2020
DOI: 10.3390/rs12111894
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Ecosystem Function Shifts in Africa Using Breakpoint Analysis of Long-Term NDVI and RUE Data

Abstract: Time-series of vegetation greenness data, derived from Earth-observation imagery, have become a key source of information for studying large-scale environmental change. The ever increasing length of such series allows for a range of indicators to be derived and for increasingly complex analyses to be applied. This study presents an analysis of trends in vegetation productivity—measured using the Global Inventory Monitoring and Modelling System third generation (GIMMS3g) Normalised Difference Vegetation Index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…We assume that the peak of greenness at stand basal area 10 m 2 ha −1 is explained by the dense shrub cover in this regeneration phase. Our results imply that browning trends (de Jong et al, 2013; Higginbottom & Symeonakis, 2020), are not necessarily only a sign of human disturbance (Murillo‐Sandoval et al, 2017), or drought (Anyamba & Tucker, 2005), but in some cases could also be a sign of increasing forest biomass and ecosystem recovery. Furthermore, all greening trends may not be indicative of an increase in biomass.…”
Section: Discussionmentioning
confidence: 62%
“…We assume that the peak of greenness at stand basal area 10 m 2 ha −1 is explained by the dense shrub cover in this regeneration phase. Our results imply that browning trends (de Jong et al, 2013; Higginbottom & Symeonakis, 2020), are not necessarily only a sign of human disturbance (Murillo‐Sandoval et al, 2017), or drought (Anyamba & Tucker, 2005), but in some cases could also be a sign of increasing forest biomass and ecosystem recovery. Furthermore, all greening trends may not be indicative of an increase in biomass.…”
Section: Discussionmentioning
confidence: 62%
“…As a result, different provinces show different trajectories of change and with respect to specific land-cover types (Table 3). Values of NPP for the different years under analysis in kg C m −2 are presented in Figure 6 as an aggregated indicator for overall land degradation, as has been used in previous studies (e.g., [28,39,45,48,62]). It is notable that, at this national scale, similar patterns are seen in each time slice, reflecting the influence of summer rainfall (eastern side of South Africa), winter rainfall (western fringe of South Africa) and proximity to oceanic moisture sources [63,64].…”
Section: Land-cover Changementioning
confidence: 99%
“…Remote sensing methods of mapping regional vegetation change and land degradation have been widely used across southern Africa for examining spatial and temporal variations in semi-natural ecosystems that are important for biodiversity and ecosystem services (e.g., [22,[26][27][28]44,45]). Specifically, NDVI values from time series of remote sensing data can be used to identify which regions are undergoing a decrease in NPP values [46,47] and are thus experiencing degradation, compared to those regions where NPP values are increasing (e.g., [48]). This in turn has implications for identifying sustainable development strategies for regions already experiencing climate stresses that impact on ecosystem vigor and ecosystem service provision [49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [33] used MODIS and Landsat both to analyze degradation processes in South West Niger. The authors in [34] identified shifts in vegetation productivity in African savannahs by applying BFAST on GIMMS NDVI. The authors in [6] used BFAST on the Landsat-derived moisture index to detect vegetation degradation in the Kavango-Zambezi Transfrontier Conservation Area (KAZA).…”
Section: Introductionmentioning
confidence: 99%